Tính \(L=\lim\left(\sqrt{n^2-1}-\sqrt{3n^2+2}\right)\).
\(-2\) | |
\(0\) | |
\(-\infty\) | |
\(+\infty\) |
Chọn phương án C.
Dùng máy tính cầm tay:
Chọn phương án C.
\(\begin{aligned}
L&=\lim\left(\sqrt{n^2-1}-\sqrt{3n^2+2}\right)\\
&=\lim\left(\sqrt{n^2\left(1-\dfrac{1}{n^2}\right)}-\sqrt{n^2\left(3+\dfrac{2}{n^2}\right)}\right)\\
&=\lim\left(n\sqrt{1-\dfrac{1}{n^2}}-n\sqrt{3+\dfrac{2}{n^2}}\right)\\
&=\lim n\cdot\left(\sqrt{1-\dfrac{1}{n^2}}-\sqrt{3+\dfrac{2}{n^2}}\right)\\
&=-\infty.
\end{aligned}\)
Vì \(\begin{cases}
\lim n&=+\infty\\
\lim\left(\sqrt{1-\dfrac{1}{n^2}}-\sqrt{3+\dfrac{2}{n^2}}\right)&=1-\sqrt{3}<0.
\end{cases}\)